Experimental and Theoretical Studies on the Adsorption and Desorption Mechanisms of Chromate Ions on Cross-Linked Chitosan - Kenji Mishima; Xiaoyu Du; Shunsuke Sekiguchi; Naoki Kano (Journal of Functional Biomaterials, 2017)
In this work, chitosan bead materials were modified by cross-linking with epichlorohydrin (EP) and glutaraldehyde (GA) for the removal of heavy metals in wastewater. Using these cross-linked chitosan materials, the dependence of adsorption of chromate anions on pH was investigated experimentally and theoretically. The experimental results show that the adsorption process of the chromate (Cr) ions greatly depends on the pH of the solution, with the chitosan modified by cross-linking being an efficient adsorbent for chromate. On the other hand, quantum chemistry calculations were conducted to find out the factor determining the pH dependence of the adsorption efficiency of chromate ions on the dimer chitosan molecule, and show results similar to those found in the experiment. Both the experimental and numerical results show that the total charge numbers of the adsorbent and the adsorbate species and their relative molecular geometries are crucial in determining the adsorption efficiency.